Machine Learning-Potato Leaf Disease Detection App (MR-PoLoD) - Fauzi, Ahmad; Chandra, Annisya E; Imammah, Sofyah; Zapata, Malvin; Marzuki, Marza I; Prayogi, Soni (ISB Atma Luhur, 2024)
Potato production in Indonesia has grown very rapidly, making Indonesia the largest potato producer in Southeast Asia. However, there are challenges for farmers in growing potatoes. Such as treating potatoes for various diseases. 2 diseases will occur in potato plants if not treated quickly, namely early blight disease caused by the fungus Alternaria solani and late blight disease caused by the microorganism Phytophthora infestans. The project